Prevalence of High-risk Human Papillomavirus (HPV) Infection Among Thai Women in Lopburi, Ang Thong and Phetchabun Provinces - Kumfong, Aungkana; Taecheusai, Pawamai; Kumfong, Ittirit; Pukcharoen, Phutthalak (Journal of The Department of Medical Services, 2023)
Background: Most cases of cervical cancer are caused by infection with high risk human papillomavirus (HR-HPV) types. Objective: To study the prevalence of HR-HPV infection in Thai women in Lopburi, Ang Thong and Phetchabun Provinces. Method: It is a cross-sectional study. The data was collected from Laboratory Information system (LIS) to study in Thai women aged 30-60 years old during October 2021 to March 2022. Descriptive statistics, chi-square test and independent t-test were used to analyze. Results: 1,033 out of 18,202 women were infected with HR-HPV (5.7%). Most of those infected were 41-50 years old. Age range was significantly related to HR-HPV infection (p-value < .001). The prevalence of the HR-HPV infection in Ang Thong, Lopburi and Phetchabun was 7.5%, 6.6%, and 4.7%, respectively. The proportion of other HR HPV, 16, 18 and 16 with other HR-HPV was 71.9%, 14.9%, 5.5%, and 5.4% respectively. Among cases infected with other HR-HPV, 734 cases had abnormal results from LBC (12.1%). Those with abnormal results from Liquid-based cytology (LBC) have an average age of 45 7.45 years old. Age range was significantly related to HR-HPV infection (p-value < .01). The abnormal results from LBC in Lopburi, Phetchabun and Ang Thong was 16.3%, 11.6%, and 7.3%, respectively. Conclusion: The highest prevalence of HR-HPV infection was in Ang Thong province, followed by Lopburi and Pethchabun. It was found that the age range of 30-40 years old had the highest infection. Other HR-HPV had the highest prevalence of infection, followed by the infection from HPV types 16 and 18. Lopburi Province had the most cases with abnormal results from LBC followed by Phetchabun and Ang Thong. This study could be useful for cervical cancer surveillance programs, the development of cervical cancer screening system, and guidelines on cervical cancer vaccine management.